Pengaruh Model Pembelajaran terhadap Motivasi Belajar Matematika Siswa - Haeriah Hamka; Baso Intang Sappaile; Hisyam Ihsan (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2017)
This research is a quasi experiment which involved two groups with different treatment. Objectives of this research were to know the students’ mathematics learning motivation between the application of conventional and hypnoteaching learning models on students grade X. The population in this research is students grade X in State Senior High School in Makassar, South Sulawesi and then two schools and two classes are selected by cluster random technique as research sample. Data analysis by using descriptive and inferential statistics. The result was obtained the improving of mathematics learning motivation on students who taught by using hypnoteaching learning model is greater than the improving of mathematics learning motivation on students who taught by using conventional learning model.